Fartlek Exercises On Aerobic Resistance - M Haris Satria (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
The problem in this research is the level of aerobic endurance of football players at Bina Darma University which is not good. The study was conducted to determine whether fartlek training can increase the aerobic endurance of Bina Darma University football players. This research is an experimental research. The instrument used was the blepp test. The data analysis used SPSS statistics 23. The result of t_ (count) = 11.115> t_ (table) = 1.740 so that it states that fartlek training can increase the aerobic endurance of Bina Darma University football players.